2021
DOI: 10.20944/preprints202112.0088.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polycystic Ovary Syndrome: An Evolutionary Adaptation to Lifestyle and the Environment

Abstract: Polycystic ovary syndrome (PCOS) is increasingly recognized as a complex metabolic disorder that manifests in genetically susceptible women following a range of negative exposures to nutritional and environmental factors related to contemporary lifestyle. The hypothesis that PCOS phenotypes are derived from a mismatch between ancient genetic survival mechanisms and modern lifestyle practices is supported by a diversity of research findings. The proposed evolutionary model of the pathogenesis of PCOS incorporat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 206 publications
(353 reference statements)
0
13
0
Order By: Relevance
“…As a class of agents, synbiotics have a growing evidence base for the treatment of obesity [ 104 ], gestational diabetes [ 105 ], type 1 [ 106 ], and type 2 diabetes [ 107 ]. It is not surprising that synbiotics have also been evaluated in the treatment of women with PCOS, since PCOS is part of this related cluster of metabolic conditions [ 5 , 108 110 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As a class of agents, synbiotics have a growing evidence base for the treatment of obesity [ 104 ], gestational diabetes [ 105 ], type 1 [ 106 ], and type 2 diabetes [ 107 ]. It is not surprising that synbiotics have also been evaluated in the treatment of women with PCOS, since PCOS is part of this related cluster of metabolic conditions [ 5 , 108 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is both a metabolic and endocrine syndrome that affects 6–15% of reproductive-age women, or approximately 200 million globally, and is believed to be increasing in frequency [ 1 – 4 ]. PCOS is now being recognized as an ecological condition that arises in genetically susceptible women due to a mismatch between ancestral inherited adaptive genetic polymorphisms and modern lifestyle [ 5 ]. This evolving ecological view of PCOS takes into account the interaction between lifestyle and environmental factors, such as diet and activity levels, with developmentally programmed metabolic and endocrine pathways [ 3 , 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive research suggests that the etiology of PCOS involves an interaction between environmental factors and gene variants, although it has been suggested that genetic factors contribute less than 10% to disease susceptibility [26][27][28]. A large number of genetic and genome-wide association studies (GWAS) have identified common gene loci associated with PCOS phenotypes in different ethnic populations [29][30][31].…”
Section: Introductionmentioning
confidence: 99%